EFEKTIVITAS BERBAGAI PREPARAT ANTIBIOTIKA TERHADAP KASUS OMPHALITIS PADA AYAM BROILER - Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The aim of this research to know the efectivity from antibiotics to prevent and cure omphalitis cases that often happen in broiler. This research devided to five treatment groups with total of DOC (Day Old Chick) were 500 DOC. Each groups had 10 DOC with 10 repetition, so DOC total for each group were 100 DOC. Treatments approached were P1 (combination of Sulfametoksazol dan Trimetoprim), P2 (Ciprofloxacin), P3 (combination of Amoxycillin dan Collistin), P4 (Clyndamicin), and P5 (Amoxycilin). Doses for each treatments were 10 mg active compound / kg body weight or 0,1 g antibiotic / kg body weight, mixed with drank water that had given from 1 – 5 days old. Nine days old DOC were being necropted  to 10 DOC samples (10 repetition) each groups. Those organs taken were yolk sac and umbilicus. Results were analyzed descriptively with looking yolk absorbtion and size of yolk sac. Effevtive antibiotic was antibiotic that could cure omphalitis in DOC, yolk was absorbed and size of yolk sac was small or almost gone. Result showed that antibiotics of Sulfametoksazol and Trimetoprim combination had highest effectiveness than others to prevent and cure omphalitis in DOC. Keywords : Antibiotics, DOC, Yolk Sac, Omphalitis